Gait training with partial body weight support during overground walking for individuals with chronic stroke: a pilot study - Sousa, Catarina O.; Barela, Jose A. [UNESP]; Prado-Medeiros, Christiane L.; Salvini, Tania F.; Barela, Ana M. F. (Biomed Central Ltd., 2011)
Background: It is not yet established if the use of body weight support (BWS) systems for gait training is effective per se or if it is the combination of BWS and treadmill that improves the locomotion of individuals with gait impairment. This study investigated the effects of gait training on ground level with partial BWS in individuals with stroke during overground walking with no BWS.Methods: Twelve individuals with chronic stroke (53.17 +/- 7.52 years old) participated of a gait training program with BWS during overground walking, and were evaluated before and after the gait training period. In both evaluations, individuals were videotaped walking at a self-selected comfortable speed with no BWS. Measurements were obtained for mean walking speed, step length, stride length and speed, toe-clearance, durations of total double stance and single-limb support, and minimum and maximum foot, shank, thigh, and trunk segmental angles.Results: After gait training, individuals walked faster, with symmetrical steps, longer and faster strides, and increased toe-clearance. Also, they displayed increased rotation of foot, shank, thigh, and trunk segmental angles on both sides of the body. However, the duration of single-limb support remained asymmetrical between each side of the body after gait training.Conclusions: Gait training individuals with chronic stroke with BWS during overground walking improved walking in terms of temporal-spatial parameters and segmental angles. This training strategy might be adopted as a safe, specific and promising strategy for gait rehabilitation after stroke.